Proclus' hymns : essays, translations, commentary - Berg, R. M. van den 1970-. (Philosophia Antiqua, 2001)
This book studies the hymns composed by the Neoplatonist Proclus in the context of his philosophy. Its main claim is that the hymns should be understood in the context of theurgy, the ritual art adopted by the Neoplatonists in order to obtain mystical experiences. The first part of the book consists of a series of essays which discuss the relation of the hymns to Proclus' Neoplatonism, his theory of poetry, and especially to theurgy. The second part offers translations of the individual hymns together with a detailed commentary. This study will be of special interest to those working in the field of Neoplatonism and a helpful guide to scholars of Late Antique poetry and religion who wish to explore these intriguing, yet at times obscure poems.